2011
DOI: 10.1111/j.1600-0854.2011.01243.x
|View full text |Cite
|
Sign up to set email alerts
|

Derlin‐Dependent Retrograde Transport from Endosomes to the Golgi Apparatus

Abstract: Cells have to maintain stable plasma membrane protein and lipid compositions under normal conditions and to remodel their plasma membranes in response to stimuli. This maintenance and remodeling require that integral membrane proteins at the plasma membrane that become misfolded, due to the relatively harsher extracellular milieu or carbohydrate and amino acid sequence changes, are degraded. We had previously shown that Derlin proteins, required for quality control mechanisms in the Endoplasmic Reticulum, also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 71 publications
4
31
0
Order By: Relevance
“…However, it is possible that Retromer promotes futile cycling between endosomes and the Golgi, and that a sub population of ROMK is freed and recycled to the plasma membrane through alternative pathways in Retromer mutants. In fact, select cargo have been found in multiple model systems to be enriched at the plasma membrane upon Retromer inhibition (88)(89)(90) ROMK may follow a similar trafficking itinerary to that described for the Jen1 lactate permease (91). In this recent paper, the authors demonstrated that endocytosed Jen1 traffics from endosomes back to the Golgi in a Retromerdependent fashion before transiting back to the endosome and entering the MVB pathway.…”
Section: Romk Vacuolar Targeting Is Impeded In Yeast Deficient In Escmentioning
confidence: 74%
“…However, it is possible that Retromer promotes futile cycling between endosomes and the Golgi, and that a sub population of ROMK is freed and recycled to the plasma membrane through alternative pathways in Retromer mutants. In fact, select cargo have been found in multiple model systems to be enriched at the plasma membrane upon Retromer inhibition (88)(89)(90) ROMK may follow a similar trafficking itinerary to that described for the Jen1 lactate permease (91). In this recent paper, the authors demonstrated that endocytosed Jen1 traffics from endosomes back to the Golgi in a Retromerdependent fashion before transiting back to the endosome and entering the MVB pathway.…”
Section: Romk Vacuolar Targeting Is Impeded In Yeast Deficient In Escmentioning
confidence: 74%
“…Recently, RNAi-mediated repression of members of the Derlin family was shown to cause a slight resistance to ricin [26], [46] that was attributed to reduced trafficking from endosomes to the Golgi apparatus [46]. Similarly, the Derl2 deficient mutant cell line CHO-CDT R C1 displayed four-fold resistance to ricin, which was complemented by transduction with Derl2 (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Although Derlins have been most intensely studied as important factors in the translocation of ERAD substrates, these proteins have also been implicated in the trafficking of the plant toxin ricin from endosomes to the Golgi apparatus [46]. To identify which step of the CDT retrograde trafficking pathway was blocked in Derl2-deficient cells, the intracellular trafficking of Hd-CDT in parental A745TKR and mutant CHO-CDT R C1 and CHO-CDT R F1 cells was assessed by immunofluorescence microscopy as a function of time.…”
Section: Resultsmentioning
confidence: 99%
“…These observations imply that CUP-2 and Derlin-1 are involved in the quality control of transmembrane proteins at the plasma membrane, or in endocytic compartments (Schaheen et al, 2009; PMID 19509052). It was further reported that CUP-2 physically interacts with SNX-1, a subunit of the retromer complex, potentially explaining how CUP-2 is retrieved from endosomes to the Golgi (Dang et al, 2011; PMID 21722281). It was proposed that CUP-2/Derlin would further transport misfolded cargo to the ER and retranslocate it to the cytoplasm for proteasome-dependent degradation (Dang et al, 2011; PMID 21722281; Schaheen et al, 2009; PMID 19509052).…”
Section: Endocytosis: Screens and Assaysmentioning
confidence: 99%